Educational Impact of a Podcast Covering Vitreoretinal Topics: 1-Year Survey Results. (September 2019) - Venincasa, Michael J.; Cai, Louis Z.; Chang, Angela; Kuriyan, Ajay E.; Sridhar, Jayanth
Purpose: This article aims to determine preferences and demographics for listeners of an ophthalmology podcast, since podcasts are gaining favor for medical education. Methods: The present study used a cross-sectional, online survey as well as Podtrac, Inc and Squarespace, Inc platform analytics to examine perceived educational usefulness of podcasts for listeners. Results: Quarterly episode downloads increased from 684 in first-quarter 2017 to 16 016 in third-quarter 2018. A total of 102 participants completed the survey: 82 (80.4%) men and 68 (66.7%) retina attending physicians or fellows. Most respondents listened to "stay up to date" or "learn more about the field of retina" (67; 65.7% each). Most respondents agreed that podcasts are useful for medical education and result in changes in practice, but not that podcasts have surpassed traditional educational methods. For respondents, there was no difference in perceived usefulness between podcasts and peer-reviewed journals, textbooks, continuing medical education lectures, or national conferences; these did not differ with respondent listening histories. Conclusions: Podcasts are valuable adjuncts for distributing clinically relevant material.